Burkholderia cepacia in cystic fibrosis children and adolescents: overall survival and immune alterations - Shmarina, Galina; Pukhalskaya, Daria; Shmarin, Vassiliy; Semykin, Sergey; Avakyan, Lusine; Krasovsky, Stanislav; Goryainova, Anastasia; Kostyuk, Svetlana; Zinchenko, Rena; Kashirskaya, Nataliya (Frontiers in Cellular and Infection Microbiology, 2024)
Background In current literature there are only scarce data on the host inflammatory response during Burkholderia cepacia complex (Bcc) persistence. The primary objective of the present research was to carry out cross-sectional analyses of biomarkers and evaluate disease progression in cystic fibrosis (CF) patients with chronic Bcc infection and pathogen-free ones. The secondary aim was to assess prospectively overall survival of the study participants during up to 8 years of follow-up. Methods The study included 116 paediatric patients with CF; 47 CF patients were chronically infected with Bcc, and 69 individuals were Bcc free. Plasma and sputum biomarkers (neutrophil elastase, MMP-8, MMP-9, MMP-12, IL-2, IL-4, IL-6, IL-8, IL-10, IL-18, IL-22, IL-23, IL-17, IFN-γ, TGFβ1, TNF-α) were analysed using commercially available kits. Besides, inhibitory effect of dexamethasone on proliferative response of PHA-stimulated peripheral blood lymphocytes had been assessed. Results Bcc infected patients did not differ from Bcc free ones in demographic and clinical parameters, but demonstrated an increased rate of glucose metabolism disturbances and survival disadvantage during prolong follow-up period. Biomarkers analyses revealed elevated TNF-α and reduced IL-17F levels in sputum samples of Bcc infected patients. These patients also demonstrated improvement of peripheral blood lymphocyte sensitivity to steroid treatment and reduction in plasma pro-inflammatory (IL-17F and IL-18) and anti-inflammatory (TGFβ1 and IL-10) cytokine concentrations. Conclusions Reduction in IL-17F levels may have several important consequences including increase in steroid sensitivity and glycemic control disturbances. Further investigations are needed to clarify the role of IL-17 cytokines in CF complication development. Low plasma TGFβ1 and IL-10 levels in Bcc infected group may be a sign of subverted activity of regulatory T cells. Such immune alterations may be one of the factors contributing to the development of the cepacia syndrome.